Bacteremia and Pneumonia in a Tertiary PICU: An 11-Year Study. Issue 2 (February 2015) - Mathot, Femke; Duke, Trevor; Daley, Andrew J.; Butcher, Terri
Abstract : Objectives: To describe trends in aetiology and resistance patterns and patient outcomes of bacteraemia and pneumonia in a PICU over an 11-year period. We also describe interventions aimed at reducing multi-resistant infections and other serious bacterial infections in the PICU. Design and Setting: This cohort study involved data collected between January 2002 and December 2012 in the PICU of the Royal Children's Hospital in Melbourne, Australia. We documented all bacterial and fungal pathogens isolated from culture of blood or bronchial alveolar lavage fluid. Trends in aetiology and antibiotic resistance patterns were evaluated, as well as the case fatality rates of population-subgroups. Patients, Measurement and Main Results: Overall, 881 patients (8.9%) had 1, 480 serious bacterial or fungal infections and 1.2% of the PICU population suffered a multidrug-resistant infection. Twenty-six percent of 597 total deaths in the PICU during that time period were associated with a serious bacterial infection of the blood or lungs. Children in PICU with a serious infection in blood or lungs had a case fatality rate of 17.5% (95% CI, 15.0–20.2), compared with children overall in the PICU with a case fatality rate of 6.0% (95% CI, 5.5–6.5). The case fatality rate among children with multidrug-resistant sepsis was 25.6% (95% CI, 18.1–34.4) and among children with a persistent or recurrent infection in blood or lungs was 43.1% (95% CI, 30.8–56.0). Cases of multidrug-resistant bacteremia and bronchial alveolar lavage–proven pneumonia increased from 2002 to 2010 and significantly decreased from 2011, coinciding with improvements in antibiotic stewardship and infection control. Conclusions: Multiresistant bacterial sepsis and persistent or recurrent sepsis are major threats in pediatric intensive care and are associated with disproportionally high death rates. Our study describes a model for monitoring these serious infections and the effects of infection control interventions in the PICU. Abstract : Supplemental Digital Content is available in the text.